Virtual reality-based virtual lab product development in developing students' spatial abilities using the van hiele theory approach - Buchori, Achmad (Pegem Journal of Education and Instruction, 2023)
In learning during the current epidemic, students cannot meet face to face on campus, and learning geometry in universities is a dreadful lesson before the pandemic. Both at UPGRIS and other private universities so far, students are required to use a compass and ruler in making flat shapes and building spaces so they have to face to face with the lecturer, but now it can't because it is still online, so it is necessary to make learning media that aims to help students sketch flat shapes and build spaces virtually with practice making it online with a van hiele theory approach, so the resulting product is truly capable of teaching. The result of this study is a virtual geometry lab application with van Hiele theory that is valid according to material and media experts with an average score of 93 and can be used in classrooms. At PGRI University Semarang, 96% of students agreed that virtual media improved students' spatial ability. The result of this study is the application of a virtual geometry lab with van Hiele theory that is valid according to material and media experts with a score of = 93. agree that virtual media can help pupils' spatial skills. The result of this study is the application of a virtual geometry lab with van Hiele theory that is valid according to material and media experts with a score of = 93. agree that virtual media can help pupils' spatial skills.